1994
DOI: 10.1007/bf00731309
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of cell surface sialic acids modulate cell adhesion mediated by sialoadhesin and CD22

Abstract: An increasing number of mammalian cell adhesion molecules, including sialoadhesion, CD22 and the family of selectins, have been found to bind cell surface glycoconjugates containing sialic acids. Here we describe how the structural diversity of this sugar influences cell adhesion mediated by the related molecules sialoadhesin and CD22 in murine macrophages and B-cells respectively. We show that the 9-O-acetyl group of Neu5,9Ac2 and the N-glycoloyl residue of Neu5Gc interfere with sialoadhesin binding. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 193 publications
(160 citation statements)
references
References 49 publications
9
151
0
Order By: Relevance
“…Since Siglec-9 binds sialic acids with a specificity that is similar to other Siglecs (see below), the aromatic residue on the A strand cannot be an obligatory requirement for sialic acid binding by Siglecs. This would also be consistent with studies showing that naturally occurring and artificial modifications of sialic acid at the C-5 position can result in marked differences in Siglec recognition (23)(24)(25).…”
Section: Resultssupporting
confidence: 91%
“…Since Siglec-9 binds sialic acids with a specificity that is similar to other Siglecs (see below), the aromatic residue on the A strand cannot be an obligatory requirement for sialic acid binding by Siglecs. This would also be consistent with studies showing that naturally occurring and artificial modifications of sialic acid at the C-5 position can result in marked differences in Siglec recognition (23)(24)(25).…”
Section: Resultssupporting
confidence: 91%
“…Previous reports have also demonstrated that siglecs exhibit differential specificity for sialic acids commonly found in mammalian species including NeuAc, NeuGc, and 9-O-acetyl-NeuAc (3,4,29,32). Indeed, although human CD22 binds equally well to ␣2-6 sialosides containing either NeuAc or NeuGc, murine CD22 exhibits a strong preference for NeuGc (32,39,63).…”
Section: Potent Inhibition Of Mag (Siglec-4) By O-linked Sialosides-tomentioning
confidence: 96%
“…For sialoadhesin, modification of the C-8 or C-9 hydroxyl, the acetamido nitrogen or methyl group (33), or the C-1 carboxylic acid eliminated binding (Figs. 5 and 6), whereas removal of the C-4 or C-7 hydroxyl was without effect.…”
Section: Figmentioning
confidence: 99%